Tasawuf Teaching and Learning in Islamic Boarding Schools in East Kalimantan - Noorthaibah, Noorthaibah; Julaiha, Siti (Dinamika Ilmu, 2020)
Tasawuf or also called by Sufism is an integral part of Islamic religious knowledge which is particularly served in traditional even in modern conditions nowadays. A case study was done in this research in order to capture all of natural phenomenon happened in six different Islamic boarding schools in East Kalimantan particularly in Sabilarrasyad, Darul Ihsan, and An-Nur Islamic boarding schools in Samarinda, Muhammad Arsyad Al Banjari Islamic boarding school in Balikpapan, and Darul Quran wa Tarbiyah and Al Hidayah Islamic boarding schools in Kutai Kartanegara. Specifically, direct observation, semi-structured interview, as well as document study were applied in this research in order to figure out the implementation of teaching and learning of Tasawuf particularly in terms of curriculum applied, materials and media used, methods and evaluation utilized at above Islamic boarding schools. As the result, the essentials of teaching and learning of Tasawuf is directed through hidden curriculum particularly inserted in Akhlak materials taught by the teachers or what so called by Asatidz and Asatidzah at all Islamic boarding schools investigated in this research. Additionally, traditional patterns of Islamic teaching and learning of Akhlak materials are applied i.e. Bandungan, Sorogan, and Wetonan as well as conventional learning steps including Tarjamah, Pendhabitan Harakat, Imlak, Mutholaah, and Memorizing methods. Small difference in terms of media used among those Islamic boarding schools does not lead to significant highlighted aspect since all of the Kitab used is contained about Akhlak or particularly regarding with how to build positive characters, behavior, and attitude of the students. Finally, future implication is also served and discussed in this research.